(untitled) (Fiep Bulletin - online, 2012)
The quality of life is not a question only of the health sector, have to be a goal of society and the country, so that its citizens have a good life and healthy. Quality of life reflects the way the individual is adapted to the activities of their daily lives, including their State of health that involves mental and physical well-being, functional and social inclusion. Related quality of life with the feeling of well-being, autonomy, independence and personal satisfaction, which are individual and vary from one individual to another, because of its subjectivity. Goal: draw professional quality of life in basic health Units. Methods: interviews were held with questions related to the profile of the quality of life, health care and access to the instrument (WHOQOL-Bref). Search results: 240 professionals participated 27 (12%) males and 231 (88%) of females between the ages of 20 to 70 years. In relation to the quality of life of caregivers have obtained the averages regarding domains: physical (3.8), psychological (3.2), social relations (4.0), environment (3.5), quality of life and overall general health perception (3.6), whereas a good quality of life. Conclusion: evidencing through this study that the fields displayed are parts of the life of health professionals, and basic piece that should be used in the Act of caring for the elderly.